2015
DOI: 10.1111/andr.12042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the optimal vitrification protocol for pre-pubertal mice testes leading to successful in vitro production of flagellated spermatozoa

Abstract: SUMMARYTesticular tissue cryopreservation offers the hope of preserved future fertility to pre-pubertal boys with cancer before exposition to gonadotoxic treatments. The objective of this study was to compare controlled slow freezing (CSF) with five vitrification techniques for cryopreservation of murine pre-pubertal testicular tissue and to evaluate the best protocol that could provide a successful completion of spermatogenesis after in vitro maturation. Testicular tissue from 24 mice at 6.5 days post-partum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 59 publications
7
38
0
Order By: Relevance
“…One year later, the same group showed for the first time that it is possible to differentiate spermatogonia in murine pre-pubertal testes into functional sperm in vitro (Sato et al ., 2011). Since then, others have also reported similar data using murine pre-pubertal testis pieces (Dumont et al ., 2015; Arkoun et al ., 2015, 2016). …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…One year later, the same group showed for the first time that it is possible to differentiate spermatogonia in murine pre-pubertal testes into functional sperm in vitro (Sato et al ., 2011). Since then, others have also reported similar data using murine pre-pubertal testis pieces (Dumont et al ., 2015; Arkoun et al ., 2015, 2016). …”
Section: Introductionsupporting
confidence: 59%
“…However, the efficiency of the organ culture system was low, as only 0.5 ± 1.0% to 4.1 ± 3.0% of the tubules contained round spermatids exhibiting the formation of an acrosomal cap (as identified via PAS). Other recently published studies reported that murine testicular tissue cultured in organ culture resulted in 22 ± 2.8% of the tubules containing round spermatids (Dumont et al ., 2015). If repeated by others, the efficiency of murine germ cell differentiation in vitro into round spermatids would be far higher than the rats as described in this study.…”
Section: Discussionmentioning
confidence: 98%
“…(2011)2.1 M DMSO + 2.7 M EG + 0.5 M sucrose + 20% FBSSSVSpz in allografts, Spz in organotypic cultureBaert et al . (2012), Dumont et al . (2015)2.1 M DMSO + 2.7 M EG + 20% FBS + 0.5 M sucroseVial, LN2Preservation of SSCsGholami et al .…”
Section: Resultsmentioning
confidence: 99%
“…In rodents, maintenance of tissue integrity and activity in organotypic cultures was reported using slow freezing and vitrification (Travers et al ., 2011; Curaba et al ., 2011b). Complete germ cell differentiation was observed by in vitro maturation of vitrified-thawed TT fragments (Dumont et al ., 2015), as well as after grafting slow-frozen mouse and rat samples and vitrified-thawed mouse samples (Schlatt et al ., 2002; Milazzo et al ., 2010; Baert et al ., 2012; Yildiz et al ., 2013). Importantly, true validation of slow freezing as a means to preserve TT functionality came with the publication from Shinohara et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation